Representações sociais de professores do ensino fundamental sobre educação étnico-racial e as implicações em sua prática pedagógica: por uma pedagogia decolonial e intercultural - SANTOS, Antônio Luís Parlandin dos (Universidade Federal do Pará, 2019)
This thesis aimed to analyze the constitution of social representations of elementary school teachers about ethnic-racial education and the implications of their pedagogical practice. The study has as methodological theoretical reference the Theory of Social Representations with procedural approach (MOSCOVICI, 2015; JODELET, 2001). The quantitative approach is multi-method, with a descriptive and analytical methodology. We worked with ten teachers from the Municipal School of Early Childhood Education and Elementary School, located in the Guamá neighborhood of the city of Belém, Pará. Data collection techniques / information used were the Free Words Association Technique (TALP), the questionnaire and the semi-structured interview. The analysis of the data / information was made from the content analysis and the mental map. The results show that the social representations of teachers on ethnic-racial relations are expressed in the following images: School has the potential to form respect for differences; School "unprepared" to work with diversity; The school fights racism despite family education; The school is impotent in training for ethnicracial education, which comes from the family "; The teaching of Afro-Brazilian and African history and culture and education for ethnic-racial relations can contribute to the fight against racism; Racism did not remain "intact" in school over time. It has at least partially diminished; The implementation of a curriculum focused on socio-cultural diversity is still a challenge at school; Training on the subject does not prepare teachers to teach in accordance with new national guidelines; There is no adequate school planning for the development of activities that combat racism; Laws can subvert racism-related relationships in school. The meanings for this "school unpreparedness" - such as "lack of appropriate teacher training for dealing with differences / diversity, non-involvement of all actors that make up the school for the development of activities that combat racism; need to teach in school values; fact that school education is not valued by society; the school depends on society "- and the meaning for the" school that is potentially capable of training for respect for differences "- such as the school mission to educate for citizenship and contribute to a more solidary society" - were also revealed on the map mental relations about education for ethnic-racial relations as "barriers" to the concreteness of this education in school. We defend the thesis that the social representations of elementary school teachers on ethnic-racial education - in a context of socio-cultural, political-legal, economic and educational changes engendered by the Brazilian redemocratization process - present ambiguous perspectives that in some moments can reproduce racism, prejudice and racial discrimination through education, but in addition to sensitive changes to vision, a "symbolic territory" with "fertile ground" for new changes to be realized in society and in the daily school life has been built based on the intercultural perspective as a reference demanded by the students and driven by the organization and mobilization of the Black Movement.